Implementasi Pembelajaran Kitab Alalaa Sebagai Upaya Meningkatkan Kemampuan Berakhlakul Karimah Santri Madrasah Diniyah Mamba’ul Ulum Dukuh Sekuwung Desa Kedung Banteng - Theodora Jati; Maulida Agustina Hidayatul Wahidah (Social Science Academic, 2025)
Instilling akhlakul karimah values ​​in Islamic education is a very important aspect in shaping the character and personality of students. Madrasah Diniyah Mamba'ul Ulum Dukuh Sekuwung, Kedung Banteng Village, took a strategic step by implementing the study of the book Alalaa as an effort to improve the moral and ethical abilities of its students. The Alalaa Book, which contains Islamic moral teachings in depth, is used as a basis for educating students so that they not only have theoretical understanding but are also able to practice these values ​​in everyday life. This research aims to evaluate the effectiveness of implementing Alalaa book learning and its impact on the formation of akhlakul karimah behavior among students. Using a qualitative approach with a case study method, this research involved observation, interviews and documentation to collect data from students, teachers and madrasa administrators. The results of the research show that learning the book Alalaa significantly contributes to increasing the understanding and practice of akhlakul karimah by students. The implementation of interactive and contextual learning, where teaching material is linked to the reality of students' daily lives, has proven effective in instilling moral values. Although this research also identified several obstacles, such as variations in students' initial levels of understanding and limited learning time, key supporting factors such as teacher commitment, support from madrasah administrators, and a conducive learning environment succeeded in overcoming most of these obstacles. In conclusion, the implementation of learning the Alalaa book at Madrasah Diniyah Mamba'ul Ulum not only significantly improves the students' akhlakul karimah abilities, but also strengthens their moral and ethical foundations in everyday life. This research recommends the need to develop more intensive and sustainable learning programs to ensure deeper internalization of moral values